Seizure induced by tranexamic acid in a patient with chronic kidney disease on maintenance dialysis - Fuah, Kar Wah; Lim, Christopher Thiam Seong; Pang, Daniel C. L.; Jin, Shyan Wong (Wolters Kluwer Medknow Publications, 2018)
Tranexamic acid (TXA) is an antifibrinolytic agent commonly used to achieve hemostasis. However, there have been a few case reports suggesting that high-dose intravenous TXA has epileptogenic property. In patients with renal impairment, even administering the usual recommended dose of TXA can induce seizure episodes. We present here a patient on hemodialysis who developed seizures after receiving two doses of TXA over 5 h period.